Pola Komunikasi Orangtua dalam Membentuk Akhlakul Karimah Anak di Desa Bangun Purba Kecamatan Bangun Purba - Tanjung, Saydina Maya; Kholil, Syukur (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This research aims to determine parental communication patterns in shaping children's morals and morals in Bangun Purba Village, Bangun Purba District. The method used in this research is descriptive qualitative in the form of written or spoken words from people whose behavior can be observed. Data collection techniques and validity in this research used triangulation methods in the form of observation, interviews and documentation. In this research, the informants consisted of parents whose criteria were having children aged 10-16 years and were assisted by other informants, namely community religious figures. The results of the research show that the authoritarian communication patterns used by parents in Bangun Purba Village, Bangun Purba District, Deli Serdang Regency, hinder the development of children's morals. This pattern is characterized by rigid rules, lack of time together, and minimal attention, causing children not to listen to advice and not to carry out the Islamic teachings taught by their parents. To improve this, parents need to increase intensive communication with their children, be good role models, and work together with the local community, including religious leaders and educators, to strengthen children's moral development so that they grow into responsible and ethical individuals.